2018
DOI: 10.3389/fphys.2018.01062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Physiological Requirements of the Mountain Bike Cross-Country Olympic Race Format

Abstract: Objectives: To evaluate the physiological requirements imposed by the current mountain biking Cross-Country Olympic (XCO) format.Methods: Sixteen Cross-Country cyclists competing at national or international level participated in this study. All participants completed a simulated and a real official race on a cycling-accredited race track. Oxygen consumption (O2) and heart rate (HR) values expressed as %O2max and %HRmax, respectively, were divided into three physiological intensity zones. The first zone (Z1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 40 publications
1
38
0
4
Order By: Relevance
“…However, recent data collected in field conditions using advanced wearable sensor technology underline the importance of being able to repeatedly perform at metabolic rates well above V O 2peak in distance skiing as well (Gløersen et al 2018, 2019; Karlsson et al 2018). Hence, similar to XC skiing, a significant part of the race during mountain bike cross-country Olympic format is performed above maximal aerobic power (Hays et al 2018). The nature of these sports is clearly different to other endurance sports such as running or swimming in terms of energy turnover during races.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data collected in field conditions using advanced wearable sensor technology underline the importance of being able to repeatedly perform at metabolic rates well above V O 2peak in distance skiing as well (Gløersen et al 2018, 2019; Karlsson et al 2018). Hence, similar to XC skiing, a significant part of the race during mountain bike cross-country Olympic format is performed above maximal aerobic power (Hays et al 2018). The nature of these sports is clearly different to other endurance sports such as running or swimming in terms of energy turnover during races.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was state than the ventilatory parameters showed similar responses between continuous vs. intermittent protocol on that same bicycle ergometer [30]. The choice of a discontinuous protocol was made to propose an effort as similar as possible to the real XCO practice [1]. After a 5-minute warm-up at 100 Watts, the imposed power was increased by 30 Watts every 2 minutes [9].…”
Section: Protocolmentioning
confidence: 99%
“…Olympic Cross-Country mountain-biking (XCO) is a sporting discipline that requires extensive physical [1] and technical [2,3] qualities in order to perform at the highest level. It is also a sport in which equipment stands as an important factor and where the concept of optimising the man-machine interaction is essential.…”
Section: Introductionmentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted May 17, 2021. ; https://doi.org/10.1101/2021.05.17.444439 doi: bioRxiv preprint during uphill climbs is frequently above maximal aerobic power [1,3]. Biochemical analysis during simulated MTB racing showed that blood pH decreases to 7.3 and blood lactate concentration increases to 7.5 mmol/l [4]. Road cycling is of significantly longer duration and performed at a lower intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The varied static, eccentric and concentric phases of MTB [4] can be compared with the principally concentric muscle action that characterizes road cycling [11].…”
Section: Introductionmentioning
confidence: 99%